Using user emotions to trigger UI adaptation - Galindo, Julian Andres; Dupuy-Chessa, Sophie; Mandran, Nadine; Ceret, Eric (Proceedings of the ... International Conference on Research Challenges in Information Science, 2018)
User experience is an important user interface quality factor that needs to be maintained during interaction. With this goal, we propose to adapt user interfaces to users' emotions. This requires being able to detect at runtime negative emotions to trigger adaptations. However, emotions depend on users' gender and age. This makes it difficult to identify negative emotions and their cause. This paper studies the categorization of emotions depending on users' age and gender and two user experience dimensions (aesthetics and usability). Thanks to an experiment, it proposes some emotions thresholds that can be used for detecting usability and aesthetics problems from users' age and gender. These results are used in a user interface adaptation system to infer negative emotions and user interface problems.